A New Approach for the Black-Scholes Model with Linear and Nonlinear Volatilities - Gulen, Seda; Popescu, Catalin; Sari, Murat (MDPI, 2019)
Since financial engineering problems are of great importance in the academic community, effective methods are still needed to analyze these models. Therefore, this article focuses mainly on capturing the discrete behavior of linear and nonlinear Black-Scholes European option pricing models. To achieve this, this article presents a combined method; a sixth order finite difference (FD6) scheme in space and a third-order strong stability preserving Runge-Kutta (SSPRK3) over time. The computed results are compared with available literature and the exact solution. The computed results revealed that the current method seems to be quite strong both quantitatively and qualitatively with minimal computational effort. Therefore, this method appears to be a very reliable alternative and flexible to implement in solving the problem while preserving the physical properties of such realistic processes.
Keywords: Black-Scholes equation; option pricing modelling; European option; volatility; high-order finite difference; FINITE-DIFFERENCE METHOD; OPTION REPLICATION; NUMERICAL-SOLUTION; MONTE-CARLO; EQUATION; VALUATION; SCHEMES; TIME; Mathematics